Problems of the Welfare State as an Employer: Assuring the Availability and Commitment of Street-Level Bureaucrats. A Literature Review - René Lehwess-Litzmann (Social Work and Society)
Among the important trends in Western welfare states in recent decades, there is an increasing reliance on services. With services being irreducibly labor-intensive, this trend has put social workers, health and care workers, legal advisors, and other professional groups at the center stage. Only if the welfare state can attract enough qualified workers and assure their professional commitment, can it produce the public goods which most of the population have to rely on. The present text gathers insights from existing research on three key areas of regulation in which the welfare state impacts its own attractiveness as an employer: resources, the organization of work, and policy orientations. These three areas have been the stages of some historical changes which affected the work and employment situations of street-level bureaucrats; what do we know about how this affects their career decisions and dedication in their daily work?